Strategies for implementing the interRAI home care frailty scale with home-delivered meal clients - Juckett, Lisa A.; Oliver, Haley V.; Hariharan, Govind; Bunck, Leah E.; Devier, Andrea L. (Frontiers in Public Health, 2023)
Introduction: Frailty is a complex condition that is highly associated with health decline and loss of independence. Home-delivered meal programs are designed to provide older adults with health and nutritional support that can attenuate frailty risk. However, home-delivered meal agencies do not routinely assess frailty using standardized instruments, leading to uncertainty over the longitudinal impact of home-delivered meals on frailty levels. Considering this knowledge gap, this study aimed to facilitate home-delivered meal staff’s implementation of a standardized frailty instrument with meal clients as part of routine programming. This article (a) describes the use of Implementation Mapping principles to develop strategies supporting frailty instrument implementation in one home-delivered meal agency and (b) examines the degree to which a combination of strategies influenced the feasibility of frailty instrument use by home-delivered meal staff at three points. Methods and Materials: This retrospective observational study evaluated staff’s implementation of the interRAI Home Care Frailty Scale (HCFS) with newly enrolled home-delivered meal clients at baseline-, 3-months, and 6-months. The process of implementing the HCFS was supported by five implementation strategies that were developed based on tenets of Implementation Mapping. Rates of implementation and reasons clients were lost to 3- and 6-month follow-up were evaluated using univariate analyses. Client-level data were also examined to identify demographic factors associated with attrition at both follow-up time points. Results. Staff implemented the HCFS with 94.8% (n = 561) of eligible home-delivered meal clients at baseline. Of those clients with baseline HCFS data, staff implemented the follow-up HCFS with 43% of clients (n = 241) at 3-months and 18.0% of clients (n = 101) at 6-months. Insufficient client tracking and documentation procedures complicated staff’s ability to complete the HCFS at follow-up time points. Discussion. While the HCFS assesses important frailty domains that are relevant to home-delivered meal clients, its longitudinal implementation was complicated by several agency- and client-level factors that limited the extent to which the HCFS could be feasibly implemented over multiple time points. Future empirical studies are needed to design and test theoretically derived implementation strategies to support frailty instrument use in the home- and community-based service setting.